Unplugged #will you still be a Malaysian in 10 years? - Mohd. Noor Abdullah 1939-; Azrin Mohd. Noor (Sedania Corporation Sdn Bhd, 2015)
This book is a forewarning of what may happen, forcing Malaysians to re-think the past, the present and the future. The authors, Dato' Mohd Noor Abdullah, former Court of Appeal judge and a specialist in the study of the Federal Constitution, and his son, Datuk Azrin Mohd Noor, the founder and Group CEO of SEDANIA Group, alert Malaysians to the dangers of persisting with our divisive ways